Rigid Mini-Thoracoscopy Versus Semirigid Thoracoscopy in Undiagnosed Exudative Pleural Effusion: The MINT Randomized Controlled Trial. Issue 3 (July 2020) - Bansal, Shweta; Mittal, Saurabh; Tiwari, Pavan; Jain, Deepali; Arava, Sudheer; Hadda, Vijay; Mohan, Anant; Malik, Prabhat; Pandey, Ravindra Mohan; Khilnani, Gopi C.; Guleria, Randeep; Madan, Karan
Abstract : Background: There is debate regarding the ideal instrument for medical thoracoscopy. The authors compared rigid mini-thoracoscopy with semirigid thoracoscopy for thoracoscopic pleural biopsy. Methods: Consecutive subjects with undiagnosed exudative pleural effusion were randomized (1:1 ratio) to mini-thoracoscopy or semirigid thoracoscopy groups. The primary objective was a comparison of the diagnostic yield of pleural biopsy. Key secondary outcomes were the comparison of sedative/analgesic dose, operator-rated and patient-rated pain on visual analog scale (VAS), operator-rated overall procedural satisfaction (VAS), pleural biopsy size, and complications between the groups. Results: Of the 88 screened subjects, 73 were randomized: 36 to mini-thoracoscopy and 37 to semirigid thoracoscopy. Diagnostic yield of pleural biopsy in the mini-thoracoscopy (69.4%) and semirigid thoracoscopy groups (81.1%) was similar on intention-to-treat analysis ( P =0.25). Although the operator-rated overall procedure satisfaction scores were similar between groups ( P =0.87), operator-rated pain [VAS (mean±SD), 43.5±16.7 vs. 31.7±15.8; P <0.001] and patient-rated pain (VAS, 41.9±17.3 vs. 32.1±16.5; P =0.02) scores were greater in the mini-thoracoscopy group. Mean dose of fentanyl and midazolam received was similar between the 2 groups ( P =0.28 and 0.68, respectively). Biopsy size was larger in the mini-thoracoscopy group (16.1±4.5 vs. 8.3±2.9 mm; P <0.001). Three minor complications occurred in the mini-thoracoscopy group and 6 in the semirigid thoracoscopy group ( P =0.11). There were no serious adverse events or procedure-related mortality. Conclusion: Diagnostic yield of rigid mini-thoracoscopy is not superior to semirigid thoracoscopy. Use of semirigid thoracoscope may provide greater patient comfort.